Childhood corporal punishment in Bahamian college students: Association with executive functions, mood, sensitivity to reward and punishment, openness to experience, and creativity - Fielding, William J.; Abecassis, Maurissa; Isquith, Peter K.; Roth, Robert M. (International Journal of Bahamian Studies, 2025)
Corporal punishment (CP) of children remains a common means of punishment in Caribbean families despite increasing evidence of long-term negative repercussions. We evaluated whether college students with and without a history of childhood CP differed with respect to self-rated executive functions (EF), mood, sensitivity to reward/punishment, openness to experiences, and creativity. Participants were 454 students at University of The Bahamas. They completed an anonymous online survey that included the Discipline Questionnaire, Behavior Rating Inventory of Executive Function – Adult, Depression Anxiety Stress Scale-21, Sensitivity to Reward and Sensitivity to Punishment Questionnaire, NEO-FFI-3 Openness scale, and Runco Ideational Behavior Scale - Short Form. A total of 84.8% received CP, more commonly in childhood (80.6%) than adolescence (53.1%). Overall, those who received CP endorsed worse EF and more emotional distress. CP during childhood (ages 5-12) was related to worse depression and aspects of EF. CP during adolescence was associated with more anxiety, depression, and stress, greater difficulty with all aspects of EFs, as well as lower sensitivity to reward or punishment. More severe CP was related to greater self-rated creativity and openness. CP during childhood, and especially adolescence, is associated with adverse effects in college students including their emotional and executive functioning, as well as responsiveness to motivational stimuli. Greater creativity and openness may reflect a means to cope with a history of CP. These findings, coupled with other research, indicate that the current tolerance of CP in The Bahamas is unfounded and policies should be changed accordingly.